Brand Experience and Psychological Determinants of Loyalty in Chinese Smart Tablet Brands - Ripaldi Krisnanta Hidayat; Djose Kaban; Kurniawati Kurniawati (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Amid intensifying competition in the technology market, understanding the drivers of consumer loyalty has become increasingly critical for brands. This research investigates how brand experience shapes brand loyalty among Indonesian users of Chinese smart tablets. It analyzes four psychological pathways brand love, brand satisfaction, self-brand connection, and brand trust within the Stimulus–Organism–Response (S–O–R) framework. The study evaluates whether brand experience directly promotes loyalty or works through internal psychological processes. Using survey data from 310 respondents, analyzed with Structural Equation Modeling (SEM) in AMOS, the findings show that brand experience strongly enhances brand love, brand satisfaction, self-brand connection, and brand trust, but lacks a direct effect on brand loyalty. Additional analysis reveals that only brand satisfaction, self-brand connection, and brand trust are significant mediators; brand love does not mediate this relationship. The discussion interprets these results through psychological mechanisms triggered by brand experience, emphasizing how affective, cognitive, and identity-based processes contribute to loyalty. The study offers insights into the psychological pathways linking brand experience and loyalty in technology markets.